Объективные и субъективные факторы психологического благополучия (Польша, Венгрия, Грузия, Украина) - Погорелая, Н.; Диева, Т. (Социология: теория, методы, маркетинг, 2007)
The paper encloses two theoretical approaches to the psychological well-being problem, such as social comparison theory and theory of needs, which were used in the comparative survey "Social Tension in Age Groups: Tension between Aspirations and Possibilities" performed in Hungary, Poland, Ukraine, and Georgia at the end of 2005 — beginning of 2006. Analysis of the survey data enables to make some conclusions. Firstly, reference point that allows comparing one's own living conditions with the others' standards of life exerts a rather significant influence on psychological well-being in the countries with less successful economic reforms (Ukraine and Georgia). At the same time, no relationship was established between psychological well-being and a reference group in Poland and Hungary reputed to be "transformation leaders". Moreover, none of the above-mentioned approaches could explain how people from different countries determined their reference points.